2001
DOI: 10.1023/a:1017587727533
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: The effects of new taurine derivatives TAU-15 and TAU-60 with normal and branched alkyl chains, respectively, in a dose of 25 mg/kg on the primary immune response in rats were studied in rats. Intraperitoneal injections of test compounds for 24 days caused transient inhibition of immune reactions to thymus-dependent antigen, which was related to suppressed production of interleukin-1beta playing a key role in antigen presentation. This effect was probably associated with activation of cortisol secretion. TAU-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…The increased excretory function of adrenal glands in rats chronically exposed to energy drinks may be partially related also to taurine—according to Sapronov et al, taurine derivatives increase cortisol secretion. [ 27 ]. It has lately been reported that taurine itself causes increase in corticosterone levels in rats [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased excretory function of adrenal glands in rats chronically exposed to energy drinks may be partially related also to taurine—according to Sapronov et al, taurine derivatives increase cortisol secretion. [ 27 ]. It has lately been reported that taurine itself causes increase in corticosterone levels in rats [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…In particular, taurine-deficient cats presented significant leukopenia, decreased respiratory burst in neutrophils, and depletion of cells from B cell areas in lymph nodes and splenic follicle centers ( 32 ). Apart from leukopenia, taurine deficiency proved to cause functional defects of the neutrophils and decreased phagocytosis of microorganisms such as Staphylococcus epidermis ( 5 , 33 ). Conversely, taurine was reported to mediate its ameliorative effect on age-related decline in the proliferative ability of lymphocytes through increasing calcium levels.…”
Section: The Role Of Taurine In Inflammationmentioning
confidence: 99%
“…In particular, the effect of taurine was more potent on T-cells, that were more susceptible to age-related decline in proliferation than B lymphocytes ( 32 ). The effect of taurine on lymphocyte function was substantiated through its chaperoning role concerning MHC class II antigen expression ( 33 ). The aforementioned data were evaluated given that T-cell proliferation is mediated independently of the age-related alteration in taurine transport ( 34 ).…”
Section: The Role Of Taurine In Inflammationmentioning
confidence: 99%
“…muscles) and act as nutrients for cells of the immune system and also for the synthesis of taurine, glutathione and acute phase protein (APP) [163]. Taurine is found in inflammatory cells e.g.…”
Section: (N) Modulation Of the Immune Systemmentioning
confidence: 99%